2017
DOI: 10.3892/ol.2017.7199
|View full text |Cite
|
Sign up to set email alerts
|

miR‑203a suppresses cell proliferation by targeting E2F transcription factor 3 in human gastric cancer

Abstract: Abstract. MicroRNAs (miRs) are a class of short non-coding RNAs that serve an essential role in the tumorigenesis of gastric cancer (GC). MiR-203a has been reported as a tumor repressor in various types of human cancer. In the present study, the function of miR-203a on the proliferation of GC cells was investigated. Bioinformatics analyses revealed that miR-203a targets the 3'-untranslated region of E2F transcription factor 3 (E2F3) messenger RNA. A luciferase reporter assay and western blot analysis were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
(22 reference statements)
1
31
0
Order By: Relevance
“…E2F3 is a member of the E2F family and serves as a transcription factor that could play an important role in cell proliferation, apoptosis and so on [22]. Numerous studies have shown that E2F3 functions in the control of tumor progression and is increased in different kinds of cancers [23][24][25][26].Consistent with previous studies, the present study found that E2F3 was increased in PANC-1 cells. Additionally, knockdown of E2F3 could reduce proliferation and invasion and promote apoptosis of PANC-1 cells.…”
Section: Discussionsupporting
confidence: 91%
“…E2F3 is a member of the E2F family and serves as a transcription factor that could play an important role in cell proliferation, apoptosis and so on [22]. Numerous studies have shown that E2F3 functions in the control of tumor progression and is increased in different kinds of cancers [23][24][25][26].Consistent with previous studies, the present study found that E2F3 was increased in PANC-1 cells. Additionally, knockdown of E2F3 could reduce proliferation and invasion and promote apoptosis of PANC-1 cells.…”
Section: Discussionsupporting
confidence: 91%
“…Abundant investigations have suggested that E2F3 participates in tumor growth. For example, miR‐203a inhibits gastric cancer cell proliferation by targeting E2F3 24 . LncRNA NEAT1 modulates non–small cell lung cancer progression by sponging miR‐377 to regulate the E2F3 expression 25 .…”
Section: Discussionmentioning
confidence: 99%
“…We identified miR-203a-3p, an important regulator in cancers [17-22], as a potential target miRNA of HOTAIR. The binding site between miR-203a and HOTAIR is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The crosstalk between lncRNAs and miRNAs has been reported to control cancer progression [21]. miR-203a has been found to be a crucial regulator involved in various cancers, such as gastric cancer [22], nasopharyngeal carcinoma [23], breast cancer [24], lung cancer [25], live cancer [26], and CRC [27]. However, the potential involvement of miR-203a in the chemoresistance of CRC is not well known.…”
Section: Introductionmentioning
confidence: 99%